Study on Mechanism of Surfactant Adsorption at Oil–Water Interface and Wettability Alteration on Oil-Wet Rock Surface - Xinyu Tang; Yaoyao Tong; Yuhui Zhang; Pujiang Yang; Chuangye Wang; Jinhe Liu (Molecules)
With the depletion of conventional light crude oil reserves in China, the demand for heavy oil exploitation has grown, highlighting the increasing significance of enhanced heavy oil recovery. Surfactants reduce oil–water interfacial tension, modify the wettability of reservoir rocks, and facilitate the emulsification of heavy oil. Consequently, investigating the adsorption behavior of surfactants at oil–water interfaces and the underlying mechanisms of wettability alteration is of considerable importance. In this study, the surface tension of four surfactants and their interfacial tension with Gudao heavy oil were measured. Among these, BS-12 exhibited a critical micelle concentration (CMC) of 6.26 × 10−4 mol·dm−3, a surface tension of 30.15 mN·m−1 at the CMC, and an adsorption efficiency of 4.54. In low-salinity systems, BS-12 achieved an ultralow interfacial tension on the order of 10−3 mN·m−1, demonstrating excellent surface activity. Therefore, BS-12 was selected as the preferred emulsifier for Gudao heavy oil recovery. Additionally, FT-IR, SEM, and contact angle measurements were used to elucidate the interfacial adsorption mechanism between BS-12 and aged cores. The results indicate that hydrophobic interactions between the hydrophobic groups of BS-12 and the adsorbed crude oil fractions play a key role. Core flooding experiments, simulating the formation of low-viscosity oil-in-water (O/W) emulsions under reservoir conditions, showed that at low flow rates, crude oil and water interact more effectively within the pores. The extended contact time between heavy oil and the emulsifier led to significant changes in rock wettability, enhanced interfacial activity, improved oil recovery efficiency, and increased oil content in the emulsion. This study analyzes the role of surfactants in interfacial adsorption and the multiphase flow behavior of emulsions, providing a theoretical basis for surfactant-enhanced oil recovery.